Disjoint geographical distribution of intertidal and nearshore benthic invertebrates in the Southern Hemisphere Distribuciones geográficas disyuntas de invertebrados bentónicos intermareales y del submareal somero en el Hemisferio Sur - JUAN C CASTILLA; RICARDO GUIÑEZ (Revista Chilena de Historia Natural, 2000)
Biogeographical explanations for the extant and paleo disjoint geographical distribution in the southern hemisphere of five species of nearshore marine benthic invertebrates: Gaimardia trapesina, Ostrea chilensis, Pyura stolonifera taxonomic complex, Aulacomya ater and Concholepas concholepas, showing distinctive reproductive strategies and early life history characteristics are reviewed and analyzed. Through the use of published and new information we contrasted the following hypotheses: a) vicariance-historical process, b) epiplanktonic larval dispersal, c) juvenile/adult dispersal through rafting and d) planned or accidental anthropogenic dispersal mechanisms. The juvenile/adult transoceanic dispersal hypothesis by rafting was the only one impossible to be rejected for the species analyzed. The implication and future direction for research in this area are discussed Se revisa y analiza las posibles explicaciones para la distribución geográfica disyunta, presente y pasada, en el hemisferio sur de cinco especies de invertebrados bentónicos marinos litorales: Gaimardia trapesina, Ostrea chilensis, el complejo taxonómico Pyura stolonifera, Aulacomya ater y Concholepas concholepas, con estrategias reproductivas y características de historia de vida distintas. Se discute y pone a prueba, usando información original o publicada, las siguientes hipótesis: a) procesos históricos de vicarianza, b) dispersión de larvas epi-planctónicas, c) dispersión de juveniles o adultos por transporte pasivo y d) dispersión antropogénica planificada o accidental. La hipótesis de dispersión transoceánica de juveniles o adultos fue la única imposible de rechazar para las especies analizadas. Se discute las direcciones futuras de investigación en esta área